Improving Farmers’ Digital Literacy for Packaging and Product Imaging in Competitive Agricultural Markets - Damayanti, Adhisty Puri; Sari, Erlina Novita; Saputri, Diana; Irawan, Norbertus Citra; Budiyono, Agus (Universitas Tunas Pembangunan Surakarta, 2025)
Smallholder farmers face persistent challenges in adding value to their agricultural products due to limited access to digital marketing knowledge and skills. Many of these farmers struggle to connect their production activities with current market demands, resulting in low product appeal and reduced income. This community service program aimed to bridge that gap by introducing digital capacity-building in packaging and product promotion. The team designed a participatory learning method that combined visual presentations, product demonstrations, and guided discussions to improve farmers’ understanding and motivation. The facilitators conducted the training at a rural farmer group in Jumapolo, involving 30 participants from various age groups. The team collected data using pre- and post-training questionnaires focused on knowledge, attitude, and behavioral intention. The Kruskal-Wallis H Test was used to analyze the differences in post-intervention score across age groups. The analysis revealed a significant improvement in learning outcomes, particularly among younger participants who were more receptive to digital tools and practices. The observations in the field also showed that younger farmers actively engaged in hands-on sessions, while older farmers preferred visual learning and peer support. This program demonstrated that digital empowerment efforts can be practical when tailored to different learning profiles. Future community programs should consider adopting segmented approaches and implementing intergenerational mentoring to ensure the inclusive adoption of digital marketing skills. Policymakers and agricultural institutions must support continuous learning models that connect production with market access through practical, user-friendly digital training.